2013
DOI: 10.1002/ajmg.a.36188
|View full text |Cite
|
Sign up to set email alerts
|

Embryonic left–right separation mechanism allows confinement of mutation‐induced phenotypes to one lateral body half of bilaterians

Abstract: A fundamental question in developmental biology is how a chimeric animal such as a bilateral gynandromorphic animal can have different phenotypes confined to different lateral body halves, and how mutation-induced phenotypes, such as genetic diseases, can be confined to one lateral body half in patients. Here, I propose that embryos of many, if not all, bilaterian animals are divided into left and right halves at a very early stage (which may vary among different types of animals), after which the descendants … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 123 publications
(249 reference statements)
0
15
0
Order By: Relevance
“…Individuals with congenital hemidysplasia with ichthyosiform erythroderma and limb defects (CHILD) syndrome exhibit striking demarcation of affected and unaffected tissue along the midline (Figure 2A) [7]. The exact time of left-right separation in humans is unknown [8]; in mice it appears to occur near the 8-cell stage [9]. If mutant cells arise before determination and are present on both sides of the left-right axis, tissues on both sides of the individual can be affected, potentially including one or both gonads (Figure 1B).…”
Section: Developmental Timing Of Mutationmentioning
confidence: 99%
“…Individuals with congenital hemidysplasia with ichthyosiform erythroderma and limb defects (CHILD) syndrome exhibit striking demarcation of affected and unaffected tissue along the midline (Figure 2A) [7]. The exact time of left-right separation in humans is unknown [8]; in mice it appears to occur near the 8-cell stage [9]. If mutant cells arise before determination and are present on both sides of the left-right axis, tissues on both sides of the individual can be affected, potentially including one or both gonads (Figure 1B).…”
Section: Developmental Timing Of Mutationmentioning
confidence: 99%
“…Moreover, embryonic left-right separation is an important event during embryogenesis of bilaterians. In a recent study, by analyzing multiple lines of molecular and cell biology evidence, Ma concluded that embryos of bilaterians are divided into left and right lateral halves at or shortly after 8-cell stage [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Avian gynandromorphs exhibit distinct male/female trait demarcation along the midline (Aw and Levin, 2008;Vandenberg and Levin, 2013) suggesting that the midline and, therefore, a distinct left-right axis, is established at the first cell division. Analysis of incomplete chicken gynandromorphs, however (Zhao et al, 2010), suggests that asymmetry is not established until the eight-cell stage (Ma, 2013). Subsequent to establishing the midline, it has been demonstrated that PCP signaling during the formation of the primitive streak (1-3HH; Hamburger and Hamilton, 1951), establishes the polarization of cells toward the primitive streak and, therefore, confers unique cellular identity in the left and right axis, perturbation of which disrupts subsequent asymmetrical expression of SHH (Zhang and Levin, 2009).…”
Section: Introductionmentioning
confidence: 99%